1993
DOI: 10.3109/10826089309039632
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerabilities and Cultural Change: Drug Use among Puerto Rican Adolescents in the United States

Abstract: The investigations examined drug usage-based and culture-based differences in young Puerto Ricans living in New York (100 nonusers and 192 drug users), Americans living in New York (100 nonusers and 99 drug users), and Puerto Ricans living in Puerto Rico (100 nonusers and 98 drug users). The Associative Group Analysis method was used to measure cultural change in three dimensions: dominant perceptions, priorities, and evaluations. The findings show that the Puerto Rican drug user and nonuser groups in New York… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 13 publications
2
16
1
Order By: Relevance
“…11,27 To our knowledge, this preliminary study was the first to use picture cues to examine both implicit and explicit drug related cognition in young adults who were cocaine dependent polydrug users, compared to a similarly aged group with limited lifetime exposure to drugs. Consistent with previous studies demonstrating that cocaine users associate cocaine with positive experiences and feelings 79 , the cocaine dependent polydrug users in the current study rated the drug related visual information as more likable than the controls. The cocaine group also found the drug cues more arousing, as Wiers et al 10 observed for cocaine words.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…11,27 To our knowledge, this preliminary study was the first to use picture cues to examine both implicit and explicit drug related cognition in young adults who were cocaine dependent polydrug users, compared to a similarly aged group with limited lifetime exposure to drugs. Consistent with previous studies demonstrating that cocaine users associate cocaine with positive experiences and feelings 79 , the cocaine dependent polydrug users in the current study rated the drug related visual information as more likable than the controls. The cocaine group also found the drug cues more arousing, as Wiers et al 10 observed for cocaine words.…”
Section: Discussionsupporting
confidence: 90%
“…Within this context, results of past studies, together with those of the present study, provide evidence for implicit cognitive processing in chronic drug users that is distinctive, fast, and positively biased towards verbal and picture drug stimuli across varying extents of participant reflection on the content of the cue. The free association tasks used by Ames et al, 28,29 Stacy, 30 , Szalay et al, 79 demonstrated unique drug related implicit cognition when a first word was generated in response to a given word (e.g., cocaine) 79 or drug picture. 2830 The IAT as used by Wiers et al 10 involved assessing associations between cocaine, affect, arousal and sedation (e.g., cocaine-pleasant).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this difference was unexpected, it is attributable mainly to greater alcohol use among island Puerto Rican children, a finding that has been previously reported 1. By contrast, the greater rates of cannabis use among offspring of US migrants is a pattern that may be attributable in part to altered parenting practices or greater tolerance for the use of this substance in the mainland environment than in Puerto Rico 23 44 45. A strong association was also observed between parental and child substance use in both mainland and island Puerto Ricans.…”
Section: Discussionmentioning
confidence: 52%